Treatment of Breast Cancer With Gonadotropin-Releasing Hormone Analogs - Huerta-Reyes, Maira; Maya-Núñez, Guadalupe; Pérez-Solis, Marco Allán; López-Muñoz, Eunice; Guillén, Nancy; Olivo-Marin, Jean-Christophe; Aguilar-Rojas, Arturo (Frontiers in Oncology, 2019)
Although significant progress has been made in the implementation of new breast-cancer treatments over the last three decades, this neoplasm annually continues to show high worldwide rates of morbidity and mortality. In consequence, the search for novel therapies with greater effectiveness and specificity has not come to a stop. Among the alternative therapeutic targets, the human gonadotropin-releasing hormone type I and type II (hGnRH-I and hGnRH–II, respectively) and its receptor, the human gonadotropin-releasing hormone receptor type I (hGnRHR-I), have shown to be powerful therapeutic targets to decrease the adverse effects of this disease. In the present review, we describe how the administration of GnRH analogues are able to reduce circulating concentrations of estrogen in premenopausal women through their action on the hypothalamus-pituitary-ovarian axis, consequently reducing the growth of breast tumors and disease recurrence. Also, it has been mentioned that, regardless of the suppression of synthesis and secretion of ovarian steroids, GnRH agonists exert direct anticancer action, such as the reduction of tumor growth and cell invasion. In addition, we discuss the effects on breast cancer of the hGnRH-I and hGnRH-II agonist and antagonist, non-peptide GnRH antagonists, and cytotoxic analogues of GnRH and their implication as novels adjuvant therapies as antitumor agents for reducing the adverse effects of breast cancer. In conclusion, we suggest that the hGnRH/hGnRHR system is a promising target for pharmaceutical development in the treatment of breast cancer, especially for the treatment of advanced states of this disease.